When form follows function - Financial centres as starting points for researching the interrelationship of financial intermediaries and the management of firms - Christian Kruse (European Regional Science Association (ERSA), 2003)
Scince the 1990ies a multiplicity of young technology firms tried to enter the new markets. Some MNE`s merged or established through spin-offs new competitive firms, SME `s often found themselves in the middle of a consolidation process, developing under a strong pressure of competition new ways of legal forms and management structures such as Management-buy-outs. Capitalization, raising of capital, managing and hedging risks have become a strategic factor of success to participate in the global innovation competition. This links the system of financial intermediaries with the production- and innovation system. Firms are raising capital from the financial markets to finance their innovation and production processes through credits, bonds, stocks, venture capital, private equity and other financial products (derivates). A successful transaction is dependent on a knowledge intensive, technology based and worldwide operating system of financial intermediaries. Through ratings, risk analysis, monitoring, information processing, pricing and further more tools financial intermediaries act in their role as middlemen centres. ?Intermediaries help markets to grow by creating products that form the basis of new markets. In turn, markets help intermediaries to innovate new more customized products by lowering costs of producing them? Merton and Bodie 1995, 26). The financial innovation spiral builds up complex structures within financial markets evolve. Today, after a fatal crash of the international financial markets and the bankruptcy of hundred of national and worldwide operating firms, this has left a strong mark on the international financial landscape map. New concepts of corporate governance with demand for a stronger transparency, information policy and risk control have to be developed for a future relationship between investors, financial intermediaries and the firms management. What consequences will follow? This paper will discuss these issues from a different perspective while concentrating on some systemic backgrounds of the financial system, which shape those complex interrelationships and put them into a dynamic process. In a first step the paper is introducing a functional approach to explain institutional changes within the financial systems. Followed by the second step, some consequences and trends for financial centres with regard to their structure, functions, participants and activities will be discussed. In a third step, I try to give a framework how a financial centre could be analysed. This will open up starting points for a future research of Innovation, Financial Industry and Space (IFIS)
Keywords: 330